Association of urinary fatty acid-binding protein 1 with a rapid decline of renal function in elders with type 2 diabetes mellitus - Yu Wang; Jin Yuan; Can Zhao; Ning Li (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the relationship between urinary fatty acid binding protein-1 （u-FABP1） and a rapid decline of renal function in elders with type 2 diabetes mellitus （T2DM）. Methods From January to December 2017, 430 T2DM elders with preserved renal function were recruited for this prospective observational study. During a follow-up period of at least 5 years, they underwent a serial detection of estimated glomerular filtration rate （eGFR）. Rapid decline in renal function was defined as an annual decline of eGFR＞3 mL·min−1·（1.73m2）−1. The relationship between baseline serum level of u-FABP1 and an annual decline rate of eGFR was examined. Results During 5-year follow-ups, 70 patients （16.28%） had a rapid decline in renal function. As compared with non-rapid decline group, baseline u-FABP1 level [corrected with urinary creatinine （uCr）] of patients was significantly higher in rapid decline group [27.29（21.20, 34.03） μg/g uCr vs 39.61 （34.06, 50.0） μg/g uCr, Z = −12.240, P＜0.001]. After adjusting for such risk factors as age, gender, body mass index （BMI）, glycated hemoglobin A1c （HbA1c） and baseline eGFR, annual eGFR decline rate （%） was correlated negatively with baseline u-FABP1 （rs = −0.150, P = 0.005）. Futhermore, univariate and multivariate Logistic regression analyses indicated that age＞75 year and baseline u-FABP1≥16.76 ng/mg uCr were independent predictors of a rapid decline of renal function （P＜0.05）. When baseline level of u-FABP1 was≥22.45 ng/mg uCr, it could well predict the risk of a rapid decline of renal function. Area under receiver operating characteristic curve was 0.962 （95%CI：0.943-0.981） with a specificity of 97.10% and a sensitivity of 77.70%. Conclusions In T2DM elders with preserved renal function, elevated baseline level of u-FABP1 is associated with a high risk of rapid decline of renal function. It hints that u-FABP may play a role in the progression of early diabetic kidney disease.